SISTEM ANALISIS PENYAKIT MATA BERBASIS PHP DAN MYSQL MENGGUNAKAN METODE TF-IDF - Dicky Iskandar Sobari (STMIK SUBANG, 2022)
The development of information technology has had a positive impact on the healthcare sector, particularly in disease analysis. Eye diseases are among the health issues that require early detection for effective prevention and treatment. In this context, this research proposes the development of a PHP and MySQL-based Eye Disease Analysis System utilizing the Term Frequency-Inverse Document Frequency (TF-IDF) method. The system is designed to provide a web platform facilitating the analysis of textual data related to eye diseases. Involving PHP as the programming language and MySQL as the database, the system allows efficient storage, management, and retrieval of medical information. The TF-IDF method is employed to analyze unique characteristics within textual data, enabling the identification of symptoms, diagnosis, and treatment of eye diseases. Context Diagram, Data Flow Diagram (DFD), and Entity-Relationship Diagram (ERD) serve as visual guides in designing this system. The Context Diagram provides a general overview of the system's interaction with its external environment, while DFD illustrates the flow of data within the system. ERD is used to represent the data structure within the database. The research results are expected to significantly contribute to the efficiency of eye disease analysis, providing faster information to medical professionals and enhancing the general public's understanding of eye diseases. This system is anticipated to serve as a foundation for further developments in the application of information technology in the healthcare sector, particularly in disease analysis.